Malaria during pregnancy - Purizaca, Manuel (2015)
We present the implications of malaria in pregnancy and its effects on mother and baby. We describe the parasite’s vital cycle, the differences between endemic and non-endemic areas as pregnant women’s risks are determined by residing location. We describe pathogenesis of complications such as anemia, hypoglycemia, abortions, brain malaria, congenital malaria and placental malaria. Finally, we present treatment current technical norms and proper recommendations.